Associations of device‐measured physical activity and sedentary time with quality of life and fatigue in newly diagnosed breast cancer patients: Baseline results from the AMBER cohort study. Issue 2 (11th November 2022) - Vallance, Jeff K.; Friedenreich, Christine M.; Wang, Qinggang; Matthews, Charles E.; Yang, Lin; McNeely, Margaret L.; Culos‐Reed, S. Nicole; Bell, Gordon J.; Morielli, Andria R.; McNeil, Jessica; Dickau, Leanne; Cook, Diane; et al.
Abstract: Background: This study examined associations of device‐measured physical activity and sedentary time with quality of life (QOL) and fatigue in newly diagnosed breast cancer patients in the Alberta Moving Beyond Breast Cancer (AMBER) cohort study. Methods: After diagnosis, 1409 participants completed the SF‐36 version 2 and the Fatigue Scale, wore an ActiGraph device on their right hip to measure physical activity, and an activPAL device on their thigh to measure sedentary time (sitting/lying) and steps. ActiGraph data was analyzed using a hybrid machine learning method (R Sojourn package, Soj3x) and activPAL data were analyzed using activPAL algorithms (PAL Software version 8). Quantile regression was used to examine cross‐sectional associations of QOL and fatigue with steps, physical activity, and sedentary hours at the 25th, 50th, and 75th percentiles of the QOL and fatigue distributions. Results: Total daily moderate and vigorous physical activity (MVPA) hours was positively associated with better physical QOL at the 25th (β = 2.14, p = <.001), 50th (β = 1.98, p = <.001), and 75th percentiles (β = 1.25, p  = .003); better mental QOL at the 25th (β = 1.73, p  = .05) and 50th percentiles (β = 1.07, p  = .03); and less fatigue at the 25th (β = 4.44, p  < .001), 50th (β = 3.08, p = <.001), and 75th percentiles (β = 1.51, p = <.001). Similar patterns of associations were observed for daily steps. Total sedentary hours was associated with worse fatigue at the 25th (β = −0.58, p  = .05), 50th (β = −0.39, p  = .06), and 75th percentiles (β = −0.24, p  = .02). Sedentary hours were not associated with physical or mental QOL. Conclusions: MVPA and steps were associated with better physical and mental QOL and less fatigue in newly diagnosed breast cancer patients. Higher sedentary time was associated with greater fatigue symptoms. Abstract : Consistent and significant associations emerged between device‐measured physical activity, quality of life, and fatigue outcomes in this large cohort of newly diagnosed breast cancer patients. These results may be used to inform clinical practice and policies about incorporating physical activity and reducing sedentary time as adjuvant therapy for newly diagnosed breast cancer patients starting treatment.